Perancangan Sistem Informasi Manajemen Gudang Spare Part Berbasis Website - Qosdu Sabil; Dian Ade Kurnia; Irfan Ali (Prosiding SISFOTEK, 2025)
The rapid growth of information technology has significantly influenced industrial operations, including the petrochemical sector, where efficient spare part management is crucial to ensure continuous production. This study aims to design a web-based spare part warehouse management information system capable of managing inventory data in real-time and reducing operational inefficiencies. The system was developed using the waterfall model through several stages: requirement analysis, system design, implementation, testing, and maintenance. The application was built using PHP programming language with the Laravel framework and MySQL database. The developed system features user authentication, role-based access control, equipment and part management, stock monitoring, issue and receipt transactions, and report generation in PDF format. Testing using the black box method indicates that all functionalities perform as expected. The system enhances efficiency in spare part tracking, minimizes delays in equipment maintenance, and supports accurate stock recording. Therefore, the proposed system can be an effective solution for improving warehouse management performance within the petrochemical industry.